TREATMENT OF TRICHOMONIASIS: CLINICAL MANAGEMENT AND IMPACT ON WOMEN’S HEALTH (International Seven Journal of Multidisciplinary, 2026)
Trichomoniasis, caused by the protozoan Trichomonas vaginalis, is one of the most prevalent non-viral sexually transmitted infections (STIs) worldwide, with serious repercussions for women’s health. This narrative review analyzes contemporary clinical management, highlighting changes in therapeutic guidelines in which the metronidazole regimen (500 mg, twice daily for 7 days) has demonstrated superiority over the single 2 g dose in reducing recurrence in women. Diagnosis has evolved with the consolidation of Nucleic Acid Amplification Tests (NAATs) as the gold standard, which are essential for identifying the approximately 85% of asymptomatic cases. The study addresses the epidemiological synergy between the parasite and increased susceptibility to HIV (a 50% increase in risk), mediated by inflammatory processes and damage to the epithelial barrier, as well as serious obstetric risks such as preterm birth and premature rupture of membranes. It is concluded that effective management requires the concomitant treatment of sexual partners through Expedited Partner Therapy (EPT) and systematic screening in vulnerable populations to interrupt the chain of transmission and mitigate reproductive harm.